Determinación de la calidad de agua por bioindicadores macroinvertebrados en el Río Quindigua, parroquia Guasaganda, cantón La Maná, 2023. - Chanatasig Chicaiza, Angely Yajaira (2024)
The expansion of livestock and agriculture in the vicinity of the Quindigua River has generated significant concern about water quality, due to the introduction of both organic and inorganic pollutants. The present research project is aimed at determining water quality by bioindicators in the Quindigua River, Guasaganda Parish, La Maná canton. For this purpose, methodologies were applied that included the use of the subber net and the kick method for the identification of macroinvertebrates, whose data were used to calculate biological indices such as BMWP/col, Andean Biological, ETP, Shannon-Weaver Diversity and Simpson's. These indices allowed us to evaluate the abundance of macroinvertebrates in the Quindigua river. These indices made it possible to evaluate the abundance of species, the composition of macroinvertebrate families and the individual sensitivity of each organism, complemented with the collection of physical-chemical and microbiological data in the study area. Sampling was carried out at three points along the Quindigua River: Quindigua Bridge, Guasaganda Bridge and La Florida Bridge, during the months of November and December to cover the dry and rainy seasons, in order to compare the results in both periods. A decrease in the relationship between flow and abundance of organisms was observed during the drought, indicating a lower presence of macroinvertebrate families. The results showed that water quality was critical at Quindigua Bridge, poor at Guasaganda Bridge and fair at La Florida Bridge, with 173 macroinvertebrates collected in total. In addition, physicochemical and microbiological analyses conducted in December at La Florida Bridge revealed that dissolved oxygen conditions did not meet standards due to the high presence of organic matter. The other parameters were evaluated according to Table 3 the Tulsma Agricultural Irrigation Water Quality Criteria Book VI (Annex 1, 2015). The application of the ICA index corroborated the information from the bioindicators, classifying point one as Poor, point two as Fair and point three as Bad quality. In conclusion, these findings highlight the urgent need to implement environmental management measures and regulation of anthropological activities to preserve and improve water quality in the Quindigua River, thus ensuring the long-term health of this vital water resource.